PRMT Biology During Acute Exercise - vanLieshout, Tiffany (My University, 2017)
Protein arginine methyltransferase 1 (PRMT1), -4 (also known as coactivator-associated arginine methyltransferase 1; CARM1), and -5 catalyze the methylation of arginine residues on target proteins. In turn, these marked proteins mediate a variety of biological functions. By regulating molecules that are critical to the remodelling of skeletal muscle phenotype, PRMTs may influence skeletal muscle plasticity. Our study tests the hypothesis that the intracellular signals required for muscle adaptation to exercise will be associated with the induction of PRMT expression and activity. C57BL/6 mice were assigned to one of three experimental groups: sedentary (SED), acute bout of exercise (0PE), or acute exercise followed by 3 hours of recovery (3PE). The mice in the exercise groups performed a single bout of treadmill running at 15 m/min for 90 minutes. We observed that PRMT gene expression and global enzyme activity are muscle- specific, generally being higher in slow, oxidative muscle, as compared to faster, more glycolytic tissue. Despite the activation of canonical exercise-induced signalling involving AMPK and PGC-1α, PRMT expression and activity at the whole muscle level were unchanged. However, subcellular analysis revealed the exercise-evoked myonuclear translocation of PRMT1 prior to the nuclear translocation of PGC-1α, which colocalizes the proteins within the organelle after exercise. Acute physical activity also augmented the targeted methyltransferase activities of CARM1, PRMT1, and -5 in the myonuclear compartment, suggesting that PRMT-mediated histone arginine methylation is an integral part of the early signals that drive skeletal muscle plasticity. In summary, our data supports the emergence of PRMTs as important players in the regulation of skeletal muscle plasticity.
Keywords: Protein arginine methyltransferase; Exercise; Skeletal muscle; Fiber types; PGC-1alpha